2015
DOI: 10.1016/j.soard.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Sexual functioning and sex hormones in men who underwent bariatric surgery

Abstract: Men who lost approximately one third of their weight after Roux-en-Y gastric bypass experienced significant increases in total testosterone and SHBG. They did not, however, report significant improvements in sexual functioning, relationship satisfaction, or mental health domains of HRQoL. This pattern of results differs from that of women who have undergone bariatric surgery, who reported almost uniform improvements in sexual functioning and psychosocial status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 39 publications
3
63
0
2
Order By: Relevance
“…These changes are well maintained through the first several postoperative years. (11,16,5456) Adolescents who underwent surgery reported significant reductions in the intake of calcium, iron, folate, iron, zinc, and vitamins A and D at both 6 and 12 months postoperatively. Given the concerns about self-reported dietary intake, these observations must be viewed with caution.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are well maintained through the first several postoperative years. (11,16,5456) Adolescents who underwent surgery reported significant reductions in the intake of calcium, iron, folate, iron, zinc, and vitamins A and D at both 6 and 12 months postoperatively. Given the concerns about self-reported dietary intake, these observations must be viewed with caution.…”
Section: Discussionmentioning
confidence: 99%
“…They found that those patients with maintained relationships from pre to post-surgery, who noted improved relationship satisfaction post-surgery also had greater long-term weight loss (15). In addition to relationship stability and quality, several studies have been published that detail changes in patient sexual satisfaction following bariatric surgery (16)(17)(18)(19)(20). Of these studies, it appears that patients report increased sexual dysfunction pre-surgery (17), and women experience decreased sexual dysfunction following surgery (16).…”
mentioning
confidence: 99%
“…Both men and women report improved sexual functioning following bariatric surgery (18,20). Women also have experienced increased psychosocial outcomes including improved health-related quality of life, body image, and depressive symptoms at 2 years postsurgery (18), while men experience improved health-related quality of life, weight-related quality of life, and body image-but not relationship satisfaction (19).…”
mentioning
confidence: 99%
“…For example, Horchner and colleagues () only found statistically significant improvements on subscales of the SF‐36 assessing changes in general health perceptions, bodily pain and mental health 2 years postoperatively. In a recent study, Sarwer and colleagues found that men who underwent bariatric surgery reported statistically significant improvements in the physical health, but not the mental health domains, assessed by the SF‐36 (Sarwer et al, in press). These two studies contrast the broad improvements in HRQOL found in most other research.…”
Section: Improvements In Quality Of Life After Bariatric Surgerymentioning
confidence: 99%
“…Kolotkin and colleagues () found that gastric bypass patients reported significant improvements in weight‐related quality of life domains as compared with individuals with obesity who did not undergo surgery. In several studies, Sarwer and colleagues have found that patients report significant improvements in all specific domains of weight‐related quality of life, starting as early as 20 weeks after surgery and enduring through the first four postoperative years (Sarwer et al, ; in press).…”
Section: Improvements In Quality Of Life After Bariatric Surgerymentioning
confidence: 99%